Towards a novel content organisation in agriculture using semantic technologies: a study with topic maps as a tool. (2nd June 2009) - Patwar, Shelly; Kaur, Pritpal; Sylvester, Asil Gerard; Balaji, Venkataraman
Agricultural information management needs to be responsive to the needs of varied stakeholders, and content repurposing to suit multiple audiences is a key requirement. A framework that combines the semantic web techniques of Topic Maps (TM) and a global agricultural thesaurus, the FAO AGROVOC, has been developed on a pilot basis for five crops. The framework when overlaid on a web-based collection of information objects reveals interesting possibilities, especially in presenting the repository content in noticeably different ways to a subject-matter specialist or to an extension worker. Results are discussed and opportunities for further development are briefly described.